Pengaruh Korean Wave terhadap Generasi Muda di Indonesia - Nabila Gadis Deki Rahmadani; Xylaisyah Almeira Ali; Ayudhia Riona Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
In the development of technology like now Korean culture is quite dominating the market, not only the Indonesian market but the international market. Various kinds of products from South Korea dominate the world market ranging from fashion, makeup, skincare and culture. In its intelligence in managing exports to neighboring countries, South Korea has received international attention regarding its fall and rise in economic history, or it can be known as the “Asian Tiger”. The method used in this research is a descriptive research method that describes, records and obtains information on the current situation. The phenomenon that exists today occurs because of globalization. South Korea has intelligence in managing the economic sector so that it is able to join the World Economic Development Organization or known as the OECD. In this phenomenon that occurs, it is very good to be studied by the younger generation as an effort to prevent negative impacts that are very easy to occur in the next generation of Indonesia.